Pain Interference, Resilience, and Perceived Well-Being DuringCOVID-19: Differences Between Women With and Without Trauma Exposure Prior to the Pandemic. - Serrano-Ibáñez, Elena Rocío; Ramírez-Maestre, María del Carmen; Ruiz-Párraga, Gema Teresa; Esteve-Zarazaga, Rosa; López-Martínez, Alicia Eva (Gonzalo Martinez-Ales, 2022)
Objectives: The aim of this study was to investigate the consequences of the COVID-19 pandemic in women with non-malignant chronic pain, and to determine whether women exposed to traumatic situations prior to the outbreak would be at a higher risk of negative health impacts.Methods: A total of 365 women were divided into three subgroups according to whether or not they had experienced a traumatic event prior to COVID-19. They completed an online survey.Results: Significant differences were found between groups during lockdown: 1) more psychological abuse was experienced by the group of women who had experienced an interpersonal traumatic event prior to the pandemic than in the other subgroups; 2)physical activity levels were higher and scores on pain interference were lower in women in the non-traumatized subgroup than in the other subgroups; 3) pain interference was predicted by pain intensity, decreased social support, and resilience, whereas perceived well-being was predicted by pain interference.Conclusion: Women who had experienced a traumatic event prior to the pandemic suffered worse consequences of the COVID-19 lockdown, particularly greater pain interference, although resilience was shown to both mitigate pain interference and enhance perceived well-being
Keywords: Dolor - Aspectos psicológicos; Mujeres - Psicología; COVID-19; Women health; Trauma exposure; Pain interference; Resilience; Well-being